Effect of applied loads on passive rolling coulters for cutting crop residues - Arthur Gabriel Caldas Lopes; Aldir Carpes Marques Filho; Lucas Santos Santana; Murilo Battistuzzi Martins; Paulo Roberto Arbex Silva; José Rafael Franco; Tiago Pereira da Silva Correia; João Flávio Floriano Borges Gomides (Smart Agricultural Technology)
No-till system technology has created challenges for grain production in tropical regions, requiring alternative techniques for managing crops' residues during sowing. In context, this research aimed to relate the four straw-cutting discs effect under three vertical loads, analyzing the energy performance in corn brachiária consortium residues. A Soil Tillage Test Unit (STTU) was developed for controlled in-field tests. Three vertical load effects (2880, 3370, and 3860 N) applied to four models of cutting discs were evaluated: plain, turbo, notched, and bubble. The experimental design adopted was a Completely Randomized Design (CRD) 4 × 3 double factorial, with four cutting mechanisms and three vertical loads. ​​The evaluations included mobilized soil, working depth, average drawbar force, horizontal force per area of mobilized soil, specific force, power demanded, hourly fuel consumption, and specific fuel consumption. Positive angular coefficients were obtained for all disc models, with linear adjustment between the increase in vertical loads and force demand. Determination coefficients of 0.99 and 0.97 for Plain and Turbo discs, respectively, in addition to 0.88 for Bubble and 0.90 for Notched discs. Turbo-type discs reached the soil depths lowest. The disc model determines soil effects by depth and soil mobilized. The Turbo disc reached the soil's lowest depths. Increasing the vertical load applied to the cutting discs results in greater disturbance to the ground.